2011
DOI: 10.4049/jimmunol.1003052
|View full text |Cite
|
Sign up to set email alerts
|

Blocking of α4β7 Gut-Homing Integrin during Acute Infection Leads to Decreased Plasma and Gastrointestinal Tissue Viral Loads in Simian Immunodeficiency Virus-Infected Rhesus Macaques

Abstract: Intravenous administration of a novel recombinant rhesus mAb against the α4β7 gut-homing integrin (mAb) into rhesus macaques just prior to and during acute SIV infection resulted in significant decrease in plasma and gastrointestinal (GI) tissue viral load and a marked reduction in GI tissue proviral DNA load as compared with control SIV-infected rhesus macaques. This mAb administration was associated with increases in peripheral blood naive and central memory CD4+ T cells and maintenance of a high frequency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
127
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(135 citation statements)
references
References 57 publications
8
127
0
Order By: Relevance
“…This balance is key in tissue remodeling, thus making it pertinent that our study showed upregulation of antiproteases in the follicular phase, when the vaginal epithelium is at its thickest, and showed protease upregulation in the luteal phase, when the epithelium is much thinner. Additionally, our genomic analyses showed overexpression in the luteal phase of genes for HIV-1-enhancing proteins: syndecans (48,49), TGF-␤ (50), and a retinoic acid receptor, RARB, which facilitates upregulation of important integrins, including ␣4␤7, and other cell receptors involved in gut homing of T cells, thus enabling enhanced acquisition and dissemination of HIV-1 (51). By showing that MCP-1 was overexpressed in the follicular phase, our study supports the existence of dual roles for proteins like those reported for MIP-3␣, present in the female genital tract (52).…”
Section: Discussionmentioning
confidence: 99%
“…This balance is key in tissue remodeling, thus making it pertinent that our study showed upregulation of antiproteases in the follicular phase, when the vaginal epithelium is at its thickest, and showed protease upregulation in the luteal phase, when the epithelium is much thinner. Additionally, our genomic analyses showed overexpression in the luteal phase of genes for HIV-1-enhancing proteins: syndecans (48,49), TGF-␤ (50), and a retinoic acid receptor, RARB, which facilitates upregulation of important integrins, including ␣4␤7, and other cell receptors involved in gut homing of T cells, thus enabling enhanced acquisition and dissemination of HIV-1 (51). By showing that MCP-1 was overexpressed in the follicular phase, our study supports the existence of dual roles for proteins like those reported for MIP-3␣, present in the female genital tract (52).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, ␣4␤7 has been identified as an additional receptor molecule for HIV-1, 35 which might facilitate the initial transmission of the virus and its subsequent spread to lymphoid organs, particularly to the GALT. 36 Thus, it is conceivable that ␣4␤7 activation and proliferation induced by IL-7 could influence the levels of HIV-1 replication in the gut compartment. We are currently investigating the effects of the spontaneous rise in endogenous IL-7 and the consequent up-regulation of ␣4␤7 during the progression toward full-blown AIDS.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] The major population targeted by the virus is CD4 + T lymphocytes. Given the vital role of CD4 + T cells in the host defense against pathogens and cancer, HIVinduced progressive and chronic depletion of such T cells results in the collapse of the immune system, leading to opportunistic infections, malignancies, and ultimately death.…”
Section: The Importance Of Gastrointestinal Mucosa In Hiv Infectionmentioning
confidence: 99%